2020
DOI: 10.1177/2058738420958949
|View full text |Cite
|
Sign up to set email alerts
|

Physiological concentrations of short-chain fatty acids induce the formation of neutrophil extracellular traps in vitro

Abstract: Neutrophils represent the first line of host cellular defense against various pathogens. The most recently described microbicidal mechanism of these cells is the release of neutrophil extracellular traps (NET). Currently, a wide range of chemical and biological stimuli are known to induce this response; however, the effect of short-chain fatty acids (SCFAs) on the induction of NET is still unknown. SCFAs are produced mainly by bacterial fermentation of dietary fiber and are found in host tissues and blood. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…Furthermore, we detected a delay in NET release after HIV stimulation when neutrophils were challenged in the presence of SCFAs. In contrast to a previous report [ 81 ] showing increased NET release after neutrophil treatment with SCFAs in the mM concentration range, we did not observe any significant differences after SCFA treatment in the absence of HIV stimulation. The reason behind these disparate results remains to be determined but may be due to the different methodologies used to quantify NETs.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we detected a delay in NET release after HIV stimulation when neutrophils were challenged in the presence of SCFAs. In contrast to a previous report [ 81 ] showing increased NET release after neutrophil treatment with SCFAs in the mM concentration range, we did not observe any significant differences after SCFA treatment in the absence of HIV stimulation. The reason behind these disparate results remains to be determined but may be due to the different methodologies used to quantify NETs.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the additional link between the formation of NETs and gut microbes, a study by Liang et al in 2019 revealed that oral administration of Staphylococcal nuclease (SNase), a nuclease that degrades DNA or RNA, was capable of effectively degrading NETs in vitro and in vivo, thereby improving intestinal barrier function. More importantly, SNase alleviated the intestinal inflammatory microenvironment and averted the development of type 1 diabetes (T1D) in non-obese diabetic (NOD) mice by altering the species richness and composition of the intestinal microbiota of NOD mice [ 96 ]. Recently, a study has also shown that dominant microbes ( Acetatifactor, Coprococcus2, Lachnoclostridium_5 and Lachnospiraceae_FCS020_group ) in NOD mice had a positive correlations with neutrophils and could possibly affect T1D via NETs [ 97 ], which inspires us that further works concerning the specific mechanisms of the interaction between intestinal microbiota and NETs require more studies to be revealed.…”
Section: Nets and Intestinal Inflammationmentioning
confidence: 99%
“…In general, neutrophils are implicated in the inflammatory process related with intestinal damage in the UC model [ 111 ]. A lower pH reduced the production of Neutrophil Extracellular Traps (NET) by neutrophils [ 112 ]. The decrease of NET could be associated with an improvement in the intestinal health and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%